An Effective Bundled Approach Reduces Surgical Site Infections in a High-Outlier Colorectal Unit. Issue 1 (January 2018) - Gorgun, Emre; Rencuzogullari, Ahmet; Ozben, Volkan; Stocchi, Luca; Fraser, Thomas; Benlice, Cigdem; Hull, Tracy
Abstract : BACKGROUND: Surgical site infections are the most common hospital-acquired infection after colorectal surgery, increasing morbidity, mortality, and hospital costs. OBJECTIVE: The purpose of this study was to investigate the impact of preventive measures on colorectal surgical site infection rates in a high-volume institution that performs inherent high-risk procedures. DESIGN: This was a prospective cohort study. SETTINGS: The study was conducted at a high-volume, specialized colorectal surgery department. PATIENTS: The Prospective Surgical Site Infection Prevention Bundle Project included 14 preoperative, intraoperative, and postoperative measures to reduce surgical site infection occurrence after colorectal surgery. Surgical site infections within 30 days of the index operation were examined for patients during the 1-year period after the surgical site infection prevention bundle was implemented. The data collection and outcomes for this period were compared with the year immediately before the implementation of bundle elements. All of the patients who underwent elective colorectal surgery by a total of 17 surgeons were included. The following procedures were excluded from the analysis to obtain a homogeneous patient population: ileostomy closure and anorectal and enterocutaneous fistula repair. MAIN OUTCOME MEASURES: Surgical site infection occurring within 30 days of the index operation was measured. Surgical site infection–related outcomes after implementation of the bundle (bundle February 2014 to February 2015) were compared with same period a year before the implementation of bundle elements (prebundle February 2013 to February 2014). RESULTS: Between 2013 and 2015, 2250 abdominal colorectal surgical procedures were performed, including 986 (43.8%) during the prebundle period and 1264 (56.2%) after the bundle project. Patient characteristics and comorbidities were similar in both periods. Compliance with preventive measures ranged between 75% and 99% during the bundle period. The overall surgical site infection rate decreased from 11.8% prebundle to 6.6% at the bundle period ( P < 0.001). Although a decrease for all types of surgical site infections was observed after the bundle implementation, a significant reduction was achieved in the organ-space subgroup (5.5%–1.7%; P < 0.001). LIMITATION: We were unable to predict the specific contributions the constituent bundle interventions made to the surgical site infection reduction. CONCLUSIONS: The prospective Surgical Site Infection Prevention Bundle Project resulted in a substantial decline in surgical site infection rates in our department. Collaborative and enduring efforts among multiple providers are critical to achieve a sustained reduction SeeVideo Abstract athttp://links.lww.com/DCR/A438 .